A new individual and specific test to determine the aerobic-anaerobic transition zone (Santos Test) in competitive judokas - Santos, L.; Gonzalez, V.; Iscar, M.; Brime, J. I.; Fernandez-Rio, J.; Egocheaga, J.; Rodriguez, B.; Montoliu, M. A. (The Journal of Strength and Conditioning Research, 2010)
The main goal of this research project was to design a specific, simple, and noninvasive field test to determine the individual aerobic-anaerobic transition zone in judokas. Our aim was to develop a field test as close as possible to real judo combat. Eight state- and national-level judokas participated in the study. To find the reliability of our test, all subjects repeated the same test under the same conditions within a 7-day period. Because the results were positive, we tested the validity of our proposal using a laboratory test that possessed the same characteristics. On both tests, the same parameters were studied. The mean data obtained in the laboratory test were as follows: maximum heart rate (HRmax): 198.2 ± 3.9 b/min, HR at the anaerobic threshold: 170.3 ± 5.7 b/min, percentage of HRmax at which the anaerobic threshold appears: 85.9 ± 2.9%, lactate max: 14.6 ± 1.4 mmol/L, lactate threshold: 4 ± 0.3 mmol/L, and VO2max: 58.3 ± 4.4 ml/kg·min. The mean data obtained in the field test were as follows: HRmax: 199.7 ± 1.8 b·min-1, HR at the anaerobic threshold: 169.7 ± 2.7 b/min, percentage of HRmax at which the anaerobic threshold appears: 85.0 ± 1.8%, lactate max: 17.0 ± 2 mmol/L, lactate threshold: 4.0 ± 0.3 mmol/L, and V?O2max: 59.8 ± 3.6 ml/kg·min. There were no significant differences between the data obtained on both tests in any of the parameters evaluated, except for the lactate maximum. Therefore, we can conclude that our field test is a useful tool for judo training.